2011
DOI: 10.1371/journal.pone.0021675
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of L-Selectin Increases Atherosclerosis Development in ApoE−/− Mice

Abstract: Atherosclerosis is an inflammatory disease characterized by accumulation of leukocytes in the arterial intima. Members of the selectin family of adhesion molecules are important mediators of leukocyte extravasation. However, it is unclear whether L-selectin (L-sel) is involved in the pathogenesis of atherosclerosis. In the present study, mice deficient in L-selectin (L-sel −/−) animals were crossed with mice lacking Apolipoprotein E (ApoE −/−). The development of atherosclerosis was analyzed in double-knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Finally, the inclusion of subclinical endpoints allowed us to investigate the role of L-selectin in early atherosclerosis, as suggested by previous animal models. 4 We acknowledge limitations of this study. The number of clinical events in each ethnic group might not be sufficient to observe ethnic-specific associations of CVD events with soluble L-selectin.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Finally, the inclusion of subclinical endpoints allowed us to investigate the role of L-selectin in early atherosclerosis, as suggested by previous animal models. 4 We acknowledge limitations of this study. The number of clinical events in each ethnic group might not be sufficient to observe ethnic-specific associations of CVD events with soluble L-selectin.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies in vivo suggested a facilitating role of the membrane-bound form of this adhesion protein in leukocyte accumulation during atherogenesis; 24,25 on the contrary, in animal models of atherosclerosis lacking L-selectin, a protective role of the protein during early phases of plaque formation was observed. 4 The soluble portion of L-selectin, formed by protease shedding, is easily measurable in serum or plasma, but its specific function in atherosclerosis is difficult to interpret. In fact, circulating L-selectin was found to be protective in some studies, 7–9 and a risk factor in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, L-selectin is constitutively expressed on leukocytes. L-selectin deficiency increases size, but does not change cellular composition in atherosclerotic lesions [29], suggesting that L-selectin protects from early atherosclerosis. Therefore, three selectins mediate leukocyte rolling on inflammatory sites, but not all selectins promote atherogenesis, indicating that there exist distinct effects to three selectins.…”
Section: Leukocyte Recruitmentmentioning
confidence: 96%
“…Impaired expression balance of pro-atherogenic (proinflammatory) and anti-atherogenic (anti-inflammatory) cell markers if hyperlipidemia conditions are preserved stabilize destruction in subendothelial space. The expression of blood residual cell receptors under vascular endothelium and of vascular endothelium itself, namely: endothelin-1 [31][32][33][34][35], caveolins-1, -2, and -3 [36, 37], selectins Р (CD62P), Е (CD62E), L (CD62L), and antibodies to them on vascular endothelium, lymphocytes and platelets [38][39][40], intercellular adhesion molecule-1 (ICAM-1) marker [41][42][43], vascular cell adhesion molecule-1 (VCAM-1) marker [44][45][46][47], monocyte chemotactic protein (MCP-1) [48][49][50], macrophage colony-stimulating factor (MCSF) [51][52][53][54][55][56][57], pleiotropic cytokine (TNF-α) [58][59][60][61][62][63][64], С-reactive protein (CRP) [65][66][67][68][69][70], platelet derived growth factor (PDGF) [71][72][73][74][75][76][77], interleukin family in atherosclerosis <...>…”
mentioning
confidence: 99%